Low Literacy is not Set in Stone : Longitudinal Evidence on the Development of Low Literacy During Adulthood - Wicht, Alexandra [Verfasser]; Durda, Tabea [Verfasser]; Krejcik, Luise [Verfasser]; Artelt, Cordula [Verfasser]; Grotlüschen, Anke [Verfasser]; Rammstedt, Beatrice [Verfasser]; Lechner, Clemens M. [Verfasser] (Beltz Juventa, 2021)
"In most industrialized societies, around 10–​15% of adults are only able to read at basic levels, a phenomenon commonly termed ‘low literacy’. This study addresses two questions about the development of low literacy during adulthood: (1) How stable is low literacy in adults, that is, what share of adults experiences ascents from, or descents into, low literacy? (2) What risk and protective factors predict such ascents and descents, as well as changes in literacy within the subgroup of low-literate adults? We use large-scale data from the German National Educational Panel Study (NEPS), which provides repeated measures of adults’ literacy spanning up to six years. We identified low-literate adults based on a cut score derived using the bookmark method. We found that ascents from low literacy to higher literacy were more prevalent than descents from higher literacy to low literacy. Almost a third of low-literate adults ascended from low literacy to higher literacy after four to six years. Reading practices emerged as the most important protective factor against descents from higher literacy and predicted gains in literacy within the group of low-literate adults. Overall, our study suggests that low literacy is not an immutable condition in adulthood, but has the potential to change over an individual’s lifetime, meaning that gains in literacy over time are indeed possible among low-literate adults." (Authors' abstract, BIBB-Doku)

"In den meisten Industriegesellschaften sind etwa 10-15 % der Erwachsenen nur in der Lage, auf dem Grundniveau zu lesen, ein Phänomen, das gemeinhin als 'geringe Literalität' bezeichnet wird. Diese Studie befasst sich mit zwei Fragen zur Entwicklung geringer Literalität im Erwachsenenalter: (1) Wie stabil ist die geringe Literalität bei Erwachsenen, d.h. wie groß ist der Anteil Erwachsener, die einen Aufstieg oder einen Abstieg in den Definitionsbereich geringer Literalität erleben? (2) Welche Risiko- und Schutzfaktoren sagen solche Auf- und Abstiege sowie die Veränderungen von Literalität innerhalb der Gruppe gering literalisierter Erwachsener voraus? Wir verwenden repräsentative Daten des Nationalen Bildungspanels (NEPS), das wiederholte Messungen der Literalität Erwachsener über einen Zeitraum von vier bis sechs Jahren bereitstellt. Wir ermitteln Erwachsene mit niedriger Literalität auf der Grundlage eines Cut-Scores, der mit der Bookmark-Methode ermittelt wurde. Wir stellen fest, dass Aufstiege von geringer Literalität zu höherer Literalität häufiger waren als Abstiege von höherer Literalität zu niedriger. Die Lesepraxis erwies sich als wichtiger Schutzfaktor gegen einen Abstieg in geringe Literalität." (Autorenreferat, BIBB-Doku)
Keywords: P 1.2 Erwachsene; 370; Erwachsener; Lesekompetenz; Einflussfaktor; Alter; Bildungsniveau; Muttersprache; Nationales Bildungspanel